Peran Serta Masyarakat Desa Pulau Bengkalis dalam Mendukung Industri Kreatif Daerah dengan Berbasiskan Teknologi Informasi - Mustakim Mustakim; Eki Saputra; Trio Laksono (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Bengkalis is one of the districts in Riau Province with the potential for a Creative Economy and Creative Industries in Indonesia. The district is located on the islands with high sources of income in Riau, one of which is the Bantan District. More than 78% of Bantan people aged 17-35 are familiar with internet technology, and almost 83% of the total can operate and use internet technology. This is an attraction to develop regional potential through information and communication technology. The need for assistance and the development of online media for the community around the Bantan District is a challenge for academics and servants. The results of a survey conducted on 25 responders who were trained showed Socialization of Promotion / e-Marketing (76%), Socialization of System Operators (88%), and Socialization of System Maintenance (64). More than 80% of user responses said it was easy and could use the system that had been built. And more than 90% have supporting devices. This indicates that the activities were successful and could be applied to the study site.